Facile sol-gel derived nanostructured spinel Co3O4 as electrode material for high-performance supercapattery and lithium-ion storage. (October 2019) - Sankar Devi, Vaithiyanathan; Athika, Mattath; Duraisamy, Ezhumalai; Prasath, Arul; Selva Sharma, Arumugam; Elumalai, Perumal
Graphical abstract: Highlights: Nanostructured Co3 O4 was generated by a simple solution-based strategy using CTAB-as complexing agent. The Co3 O4 as electrode for supercapattery exhibited high energy density of 40 W h kg −1 with high Coloumbic efficiency and excellent cycle life. Sol-gel derived Co3 O4 delivered stable discharge capacity of 650 mA h g −1 at 0.2 c rate with high Coloumbic efficiency over 100 cycles. The proto-type coin cell supercapattery could power the LED bulb for more than 15 min in a single charge. Abstract: This work reports high-performance supercapattery and lithium-ion storage using nanostructured spinel cobalt oxide (Co3 O4 ) generated by modified facile sol-gel process. The formation of spinel Co3 O4 was confirmed by materials characterization techniques. Electrochemical studies of the Co3 O4 in KOH revealed excellent redox features. The supercapattery device in the form of CR-2032 coin cell consisting of the Co3 O4 as positive electrode and reduced graphene-oxide as negative electrode delivered high energy density of 40 Wh kg −1 at power density of 742 W kg −1 . In addition, the half-cell in the form of CR-2032 coin cell having the Co3 O4 as anode and lithium metal as counter electrode exhibited stabilized lithium storage capacity of 620 mA h g −1 with high Coloumbic efficiency. Glowing of a commercial LED for more than 15 min using the fabricated supercapattery was demonstrated. The nanofeatures of the sol-gel derived Co3 O4 led to such excellent charge storage and lithium storage performances.